Seawater-derived noble gases and halogens preserved in exhumed mantle wedge peridotite - Sumino, H; Burgess, R; Mizukami, T; Wallis, SR; Holland, G; Ballentine, C (2010)
Here we show how the Higashi-akaishi peridotite body in the Sanbagawa metamorphic belt, a sliver of the former mantle wedge of the eastern Eurasian plate margin, has exhumed subduction fluid noble gases and halogens with a marine pore-fluid signature from a depth of ~ 100. km. Previous work has only considered that water subduction into the mantle wedge occurs via decomposition of hydrated minerals in altered oceanic crust and sediment. The striking similarities of the observed noble gas and halogen compositions with marine pore fluids require subduction and closed system retention of marine pore fluid to at least 100. km. The Higashi-akaishi peridotites appear to have frozen-in and preserved a previously unseen part of the deep water recycling process, requiring a reassessment of the dominant transport mechanism and source of water in subduction zones. Indeed, a small proportion of marine pore fluid, preserved in the downgoing hydrous peridotite, can account for the dominant heavy noble gas isotopic and elemental composition observed in the convecting mantle. © 2010 Elsevier B.V.